1987
DOI: 10.1007/bf02109629
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic basis of a superior approach to the acetabulum with osteotomy of the ala of the ilium

Abstract: This study demonstrates the importance of a superior approach to acetabulum with intrapelvic osteotomy of the iliac ala in certain fractures of the acetabulum. This study is based on the dissection of 15 formolized and 5 frozen subjects, the surgical treatment of 17 acetabular fractures, and the performances of 2 Chiari-type osteotomies and 2 Salter-type osteotomies. We investigated the gluteus medius muscle and its pedicle in relation to the iliac ala. Landmarks for the osteotomy lines and the gluteal pedicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…The LTCL has been previously defined by Trouilloud et al 50 as having three orientations: Type A, B, and C. This study observed these same three classifications; however, the distribution of the orientations was much different than that described by Troilloud et al 50 In their series of 20 foot and ankle specimens, they found that Type A occurred in 35%, Type B in 23%, and Type C in 42% of specimens. Our study found Type A in 75%, Type B in 21%, and Type C in 4% of specimens.…”
Section: Anatomic Variantssupporting
confidence: 58%
See 2 more Smart Citations
“…The LTCL has been previously defined by Trouilloud et al 50 as having three orientations: Type A, B, and C. This study observed these same three classifications; however, the distribution of the orientations was much different than that described by Troilloud et al 50 In their series of 20 foot and ankle specimens, they found that Type A occurred in 35%, Type B in 23%, and Type C in 42% of specimens. Our study found Type A in 75%, Type B in 21%, and Type C in 4% of specimens.…”
Section: Anatomic Variantssupporting
confidence: 58%
“…Two of the ligaments were found to have varying positional attachments; LTCL and DCCL. The LTCL was documented according to the classification scheme presented by Trouillard et al 50 When the LTCL was continuous with the CFL, it was classified as Type A and occurred in 42 of 56 (75%) observed. When the LTCL was anterior and separated from the CFL, it was classified as Type B and occurred in 12 (21%) specimens.…”
Section: Ligament Anatomy and Tearsmentioning
confidence: 99%
See 1 more Smart Citation
“…RTSA was first described as a solution to treat older patients with rotator cuff tear arthropathy for which nonsurgical therapies had failed 32 . The U.S. Food and Drug Administration approved the RTSA implant for use in December 2003 for elderly patients with a rotator cuff arthropathy indication.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of reverse total shoulder arthroplasty (RTSA) was first explained by Grammont et al 32 >25 years ago. During the past 2 decades, the RTSA has been used to treat a range of complex shoulder diseases, including total shoulder arthroplasty (TSA) and hemiarthroplasty (HA) implant failures, complex proximal humeral fractures, asymmetric glenoid wear, posterior humeral head subluxation in patients with intact rotator cuffs, and irreparable rotator cuff tears in the absence of arthritis 36 .…”
mentioning
confidence: 99%